Ovarian stimulation alternatives for in vitro production of embryos in water buffaloes - Alexis Bandeo; José Luis Konrad; Natalia Vallejos; Pablo Ponce; Marina J. Sansinena; Gustavo Crudeli; Pablo Maldonado-Vargas (Revista Científica)
Currently, one of the most promising tools to increase the number of transferable embryos in buffaloes is in vitro production (IVP). However, IVP still has certain limitations that prevent its optimal efficiency for commercial application. One of these limitations is the reduced number and low competence of oocytes obtained from transvaginal follicular aspiration in this species. It has been found that ovarian stimulation with follicle- stimulating hormone (FSH) before aspiration improves the technique’s efficiency, primarily due to the increased competence of the obtained oocytes. The objective of this study was to evaluate the response to different hormonal stimulation treatments in buffalo donors, their effect on oocyte quality, and subsequent embryo production. This field study was conducted at the Pedro Antonio Silva buffalo farm, located in the General Paz department, Province of Corrientes, in 2021. A total of 60 OPU sessions were performed on Murrah and Mediterranean breed donors, and four ovarian stimulation treatments were applied. Treatment (TRT) 1, which was used as control (n=20), consisted of a day 0 insertion of an intravaginal progesterone device (IP) + 2 mg estradiol benzoate (EB) i.m., with OPU performed on day 7. Treatment (TRT) 2 (n=10) consisted of day 0 insertion of IP + 2 mg EB, followed by four applications of FSH (Folltropin-V®) i.m. with a total of 160 mg distributed in decreasing doses every 12 hours for two days (50mg, 50mg, 30mg, 30mg), OPU was then performed 36 hours after the last application. Treatment (TRT) 3 (n=20) consisted of day 0 insertion of IP + EB, followed by a day 4 application of 1050 IU of recombinant eCG (FoliRec®) i.m., OPU was performed on day 7; Treatment (TRT) 4 (n=10) consisted of day 0 insertion of IP + EB, followed by day 4 application of 2500 IU of serum eCG (Ecegon®) i.m., OPU was performed 72 hours later. Prior to each follicular aspiration, antral follicles were counted using a portable ultrasound with a linear probe (Mindray, DP30-Vet) and classified into small (≥3mm Ø), medium (4-8 mm Ø), and large (>8mm Ø) follicles. The aspirated oocytes or COCs (cumulus-oocyte complexes) were classified into grades (1 to 4) based on the number of cumulus layers present, according to the International Embryo Transfer Society method (IETS Manual). In vitro fertilization (IVF) was performed after 24 hours of oocyte in vitro maturation using cryopreserved semen from buffalo bulls of proven fertility. In vitro culture (IVC) was carried out for 6.5 days, and all embryos that reached the blastocyst stage were graded and vitrified. Descriptive statistics and analysis of variance were conducted on the obtained data, considering population and follicular size, quantity and quality of oocytes, and embryo production, with a significance level (α) of 5%. The total observed follicular population did not differ among treatments (p>0.05). However, stimulation in TRT2 (FSH) and TRT4 (serum eCG) increased the proportion of medium-sized follicles (4-8mm) available for OPU (p<0.05), which correlates with better quality. In comparison, the control group had the highest number of small follicles (<3mm). The number of collected oocytes per OPU did not vary between treatments (p>0.05). Regarding oocyte quality, TRT2 (FSH) and TRT4 (serum eCG) resulted in a higher quantity of grade 1 oocytes (p<0.05). In vitro embryo production was higher in TRT2 (1.5 embryos/buffalo/OPU), followed by TRT3 (1.05 embryos/buffalo/ OPU), and lower in TRT4 and TRT1 (0.8 and 0.6 embryos/buffalo/OPU, respectively) (p<0.05). No significant difference was found in the number of zygotes (CIV) between treatments (p<0.05), and cleavage was higher in TRT3 (p<0.05). In conclusion, this study has shown that ovarian super stimulation before OPU increases the proportion of medium-sized follicles available for the aspiration procedure, resulting in a higher proportion of viable oocytes. This effect is mainly achieved using FSH and serum eCG. Stimulation with FSH also resulted in higher rates of blastocysts and embryos produced per OPU session. These are promising for the advancement of the OPU/IVP technique in water buffaloes. Further work is needed to optimize the outcomes, especially with these new ovarian stimulation alternatives.